Translanguaging in the ESP Context: Saudi Students' Perceptions of the Bilingual Practices - Alasmari, Muhammad; Qasem, Fawaz Ali; Alhamami, Munassir (Pascasarjana Universitas Negeri Makassar, 2024)
Applied linguists address translanguaging from a variety of angles to comprehend its effectiveness, applicability, and how it supports or undermines social and educational goals in various bilingual and multilingual environments around the world. A small number of studies have been carried out to demonstrate the reality of pedagogical translanguaging in the context of higher education and, more specifically, in countries where the official language is distinct from the language of instruction in language education. Therefore, this study broadens the understanding of translanguaging practices in English for Specific Purposes (ESP) programs in Saudi universities through the perceptions and perspectives of ESP undergraduate students. The participants of this study were ESP 150 students at the University of Bisha. The data was obtained quantitatively and qualitatively using three research tools: the learners’ questionnaire, observation of teaching sessions, and semi-structured interviews with the learners. The findings indicated that students have a positive attitude towards translanguaging. They found it a useful pedagogical strategy to improve their understanding of ESP terminologies and their field-related complex terms. On the pedagogical level, the study contributed to the field of translanguaging by providing a clear picture of how students perceive translanguaging and how the use of the mother tongue along with English in the classrooms was significant in engaging the students in the learning process.